Do 2‐year changes in superior frontal gyrus and global brain atrophy affect cognition?. Issue 1 (29th August 2018) - Valdés Hernández, Maria del C.; Reid, Stuart; Mikhael, Shadia; Pernet, Cyril; ,
Abstract: Introduction: Metabolic alterations to the superior frontal gyrus (SFG) have been linked to cognitive decline. Whether these indicate structural atrophy, which could be screened for at a larger scale using noninvasive structural imaging, is unknown. Methods: We assessed annual structural magnetic resonance imaging scans and cognitive data from 3 consecutive years from 204 participants from the AD Neuroimaging Initiative database (mean age 72.24 [8.175] years). We evaluated associations between brain structural changes and performance in the Montreal Cognitive Assessment, Everyday Cognition Visuospatial subtest (ECog Visuospatial), and Functional Assessment Questionnaire. Results: Changes in the surface area of the SFG were associated with changes in the outcome of the ECog Visuospatial test ( P < .05), but an inconsistent pattern of association was found between the 2‐year global brain atrophy progression and changes in the outcome from the three cognitive tests selected. Discussion: The extent into which (and if) changes in the SFG influence cognition warrant further evaluation in a larger period in more heterogeneous population. Highlights: Two‐year superior frontal gyrus surface area changes associated with Everyday Cognition Visuospatial. Neurosynth meta‐analysis on 224 functional magnetic resonance imaging studies in‐line with our results. Changes in global atrophy inconsistently associated with Montreal Cognitive Assessment, Functional Activities Questionnaire, and Everyday Cognition visuospatial.